Antimicrobial Activities of Isothiocyanates Against Campylobacter jejuni Isolates - Dufour, Virginie; Alazzam, Bachar; Thepaut, Marion; Ermel, Gwennola; Baysse, Christine (Frontiers in Cellular and Infection Microbiology, 2012)
Food-borne human infection with Campylobacter jejuni is a medical concern in both industrialized and developing countries. Efficient eradication of C. jejuni reservoirs within live animals and processed foods is limited by the development of antimicrobial resistances and by practical problems related to the use of conventional antibiotics in food processes. We have investigated the bacteriostatic and bactericidal activities of two phytochemicals, allyl-isothiocyanate (AITC), and benzyl isothiocyanate (BITC), against 24 C. jejuni isolates from chicken feces, human infections, and contaminated foods, as well as two reference strains NCTC11168 and 81-176. AITC and BITC displayed a potent antibacterial activity against C. jejuni. BITC showed a higher overall antibacterial effect (MIC of 1.25–5 μg mL−1) compared to AITC (MIC of 50–200 μg mL−1). Both compounds are bactericidal rather than bacteriostatic. The sensitivity levels of C. jejuni isolates against isothiocyanates were neither correlated with the presence of a GGT (γ-Glutamyl Transpeptidase) encoding gene in the genome, with antibiotic resistance nor with the origin of the biological sample. However the ggt mutant of C. jejuni 81-176 displayed a decreased survival rate compared to wild-type when exposed to ITC. This work determined the MIC of two ITC against a panel of C. jejuni isolates, showed that both compounds are bactericidal rather than bacteriostatic, and highlighted the role of GGT enzyme in the survival rate of C. jejuni exposed to ITC.